Stakeholder Management of Kawasan Konservasi Mangrove dan Bekantan in Tarakan City - Rifky Edo Herlangga; Sambas Basuni (Institut Pertanian Bogor (IPB University), 2019)
Kawasan Konservasi Mangrove dan Bekantan (KKMB) is a protected area that is managed by Tarakan City Government for mangrove and proboscis monkey conservation. KKMB has a few stakeholders involved in the area. In order to create collaborative management, there must be conducted a stakeholder analysis and management. The research aimed to give stakeholder management recommendations for KKMB. Research data was collected through interviews and questionnaires. This research was also conducted to compare two methods in stakeholder analysis, Reed et al. method and Driscoll and Starik method. The result shows that Driscoll and Starik method is more objective to be used for measuring the stakeholder priority. PT Pertamina EP had to be the first priority in stakeholder management because it has great power, urgency, and legitimacy towards KKMB. In order to improve the relationship between stakeholders in KKMB there must be applied a practical strategy. This strategy strives for optimizing the area advantages for all stakeholders and also fulfill the stakeholders' needs for the area, which are facility maintenance, area sustainability improvement, and optimization of tourism activity.